Eficácia da implantação das boas práticas de preparação na qualidade microbiológica de dietas enterais de um hospital público - ALBUQUERQUE, Marinez Ferreira Barbosa (2011)
Poor hygienic sanitary conditions in the processing of enteral diets constitutes in risks of microbial contamination, and may involve complications in patients with enteral nutrition, ranging from infections digestive up to systemic infections. For this reason is important its microbiological control, whereas individuals to whom they are intended, are more susceptible to infections. Thus, this study aimed to compare the hygienic conditions of enteral diets before and after the implementation of Good Manufacturing Practices in a public hospital in Brazil. The study was developed in the Enteral Diet Unit of the Goiânia Emergency Hospital in three stages. In stage 1 before the implantation of good practices, carried out between November and December of 2008, was diagnosed the preparation conditions of the enteral diets by systematic observation of the conduct adopted by food handlers. Was applied the check list proposed by Resolution RDC nº 63 of Agência Nacional de Vigilância Sanitária/Brazil and realized microbiological analyzes of 40 samples of each element investigated: filtered water, powdered diet, reconstituted enteral diet and food handler s hand and nasal cavity culture. The good practices were implemented in phase 2, between January and June 2009, by educational training through the Maguerez Arch technical, development of Good Manufacturing Practices Handbook and by structural changes in the Enteral Diet Unit. In stage 3, between September and November 2009, was applied again the check list and repeated all microbiological analyzes carried out in the first phase, in addition the reconstituted enteral diets were analyzed at ambient temperature at Time 0 (preparation) and 1, 2, 3, and 4 hours after preparation. Both in stage 1 and 3, viable aerobic mesophilic microorganisms, total coliforms, Escherichia coli, coagulase-positive staphylococci, Staphylococcus aureus, Salmonella sp., and Pseudomonas aeruginosa were investigated. The results were compared with standards established by the Brazilian Sanitary Surveillance Legislation. Were used the software SPSS version 17.0 and STATA version 8.0 for statistical analysis and applied the McNemar test and Fisher exact test. The implementation of good practices significantly increased conformity to checklist items from 50.8% to 78.8% (p<0.001) and reduced the prevalence of contamination in the reconstituted enteral diet from 40.0% to 15.0% (p=0.031). The enteral diet could be considered safe after up to four hours at room temperature because asceptic preparation techniques were strictly followed. A significant reduction in the presence of Escherichia coli in the food handler s nasal cavity was detected (p=0.021). Conclusion: The implementation of good manufacturing practices contributed to the improvement of the enteral diet s hygienic sanitary conditions. Continued training is recommended to improve the food handlers competencies